STRATEGIC EXCELLENCE OF IRAQI PLANNING INSTITUTIONS (CASE STUDY ( - Assistant Professor Dr. Abdullah Mahmoud Abdullah; Eng. Dr. Omar Aziz Abbas; Assistant Professor Dr. Muhammad Ali Abdullah (Scholar Express Journals, 2024)
The aim of the research is to measure indicators Strategic superiority represented by (efficiency, quality of work, innovation and creativity, distinguished services, employee skills, adaptation and flexibility) and a statement of the level of response of the respondents to the researched variable and the degree of arrangement of its dimensions according to priority and importance, as well as a statement of the moral hypotheses regarding the response of the sample studied according to personal variables (age, academic qualification). (number of years of service in the current position).
Keywords: strategic superiority; quality of work; creativity and innovation